Poverty, vulnerability and quality of life in Latin America. Challenges for bioethics - León Correa, Francisco Javier (Acta Bioethica, 2011)
This article is a bibliographical review about challenges for bioethics in Latin America. First, some ethically relevant data about poverty and dependence in Latin America are presented. Afterwards, poverty and vulnerability notions are analyzed from a philosophical perspective and ethical response required, ending by examining the consequences of previous data and philosophical reflection about poverty, vulnerability and quality of life, especially in Latin American bioethics.